Exploring the social context of insomnia: a thematic content analysis of the lived experiences of insomnia of Latinx women and men - Giorgio Cosenzo, Luciana; Arias, Darwin; Alcántara, Carmela (Frontiers in Sleep, 2024)
Introduction: Although social ties have detrimental and beneficial effects on sleep health, the social processes through which social ties affect sleep remain understudied, particularly among Latinx adults. These processes include social support, social stress, social control, personal control, and symbolic meaning. Importantly, some studies suggest there are gender differences in how social ties influence Latinx health. This study explores how Latinx women and men with insomnia describe the social processes through which social ties shape their lived experience of insomnia. Methods: Qualitative data from six focus groups conducted in 2017 were analyzed using thematic content analysis. These focus groups were comprised of 35 Spanish-and English-speaking Latinx adults with insomnia. Participants were majority women (62.86%), had a mean age of 65.43 years (SD=12.63), and an average insomnia severity score of 20.6 (SD=3.44). Major and minor themes were deductively and inductively identified in the transcripts. These themes were compared between Latinx women and men. The methods and results of this study are reported using the Consolidated Criteria for Qualitative Research (COREQ).The influence of social processes on the lived experience of insomnia centered on three major themes. The first theme identified social stress and social control as precipitating and perpetuating factors of insomnia. The second theme related to how social support, through receiving advice from others, shaped participants' coping behaviors. Lastly, participants described their insomnia symptoms as negatively affecting their social relationships through social conflict. Latina women attributed their insomnia to the symbolic meaning of their gender identities, while men did not. Discussion: These findings suggest that among Latinx adults, it may be important for psychological treatments for insomnia to address the ways in which social processes contribute to insomnia symptoms. Additionally, Latina women's discussion of the influence of gender identities on their insomnia symptoms highlights the need to tailor psychological treatments for Latina women that acknowledge and address the challenges presented by traditional gender roles and expectations. Future studies should investigate the potential reciprocal relationship between social processes, mainly social stress and social control, and insomnia symptoms.